Intravenous Ascorbic Acid for the Prevention of Postreperfusion Syndrome in Orthotopic Liver Transplantation: Protocol for a Randomized Controlled Trial - Gajate, Luis; de la Hoz, Inés; Espiño, Mercedes; Martin Gonzalez, Maria del Carmen; Fernandez Martin, Cristina; Martín-Grande, Ascensión; Parise Roux, Diego; Pastor, Oscar; Villahoz, Judith; Rodriguez-Gandía, Miguel Ángel; Nuño Vazquez, Javier (JMIR research protocols, 2023)
Liver transplantation is the last therapeutic option for patients with end-stage liver disease. Postreperfusion syndrome (PRS), defined as a fall in mean arterial pressure of more than 30% within the first 5 minutes after reperfusion of at least 1 minute, can occur in liver transplantation as a deep hemodynamic instability with associated hyperfibrinolysis immediately after reperfusion of the new graft. Its incidence has remained unchanged since it was first described in 1987. PRS is related to ischemia-reperfusion (I/R) injury, whose pathophysiology involves the release of several mediators from both the donor and the recipient. The antioxidant effect of ascorbic acid has been studied in resuscitating patients with septic shock and burns. Even today, there are publications with conflicting results, and there is a need for further studies to confirm or rule out the usefulness of this drug in this group of patients. The addition of ascorbic acid to preservation solutions used in solid organ transplantation is under investigation to harness its antioxidant effect and mitigate I/R injury. Since PRS could be considered a manifestation of I/R injury, we believe that the possible beneficial effect of ascorbic acid on the occurrence of PRS should be investigated. The aim of this randomized controlled trial is to assess the benefits of ascorbic acid over saline in the development of PRS in adult liver transplantation. We plan to conduct a single-center randomized controlled trial at the Hospital Universitario Ramón y Cajal in Spain. A total of 70 participants aged 18 years or older undergoing liver transplantation will be randomized to receive either ascorbic acid or saline. The primary outcome will be the difference between groups in the incidence of PRS. The randomized controlled trial will be conducted under conditions of respect for fundamental human rights and ethical principles governing biomedical research involving human participants and in accordance with the international recommendations contained in the Declaration of Helsinki and its subsequent revisions. The enrollment process began in 2020. A total of 35 patients have been recruited so far. Data cleaning and analysis are expected to occur in the first months of 2024. Results are expected around the middle of 2024. We believe that this study could be particularly relevant because it will be the first to analyze the clinical effect of ascorbic acid in liver transplantation. Moreover, we believe that this study fills an important gap in the knowledge of the potential benefits of ascorbic acid in the field of liver transplantation, particularly in relation to PRS. European Union Drug Regulating Authorities Clinical Trials Database 2020-000123-39; https://tinyurl.com/2cfzddw8; ClinicalTrials.gov NCT05754242; https://tinyurl.com/346vw7sm. DERR1-10.2196/50091.